Molecular characterization of carbapenem- resistant Enterobacteriaceae yields increasing rates of NDM-1 carbapenemases and colistin resistance in an OXA-48- endemic area. (2nd November 2017) - Cizmeci, Zeynep; Aktas, Elif; Otlu, Baris; Acikgoz, Ozlem; Ordekci, Seyhan
Abstract : We aimed to characterize carbapenem-resistant isolates in a tertiary hospital in Istanbul, Turkey, high-prevelance area for OXA-48 producers. About 76 Enterobacteriaceae clinical isolates were included. Carbapenemase production was detected by Carbapenem Inactivation Method and carbapenemase genes were investigated by PCR. The clonal relationships were evaluated by AP-PCR. Nineteen Klebsiella pneumoniae isolates were colistin resistant. About 75 isolates yielded carbapenemase by CIM. 52 OXA-48, 17 NDM-1 and 2 VIM-5 carbapenemase genes were detected. Co-production of 'OXA-48 and NDM-1' and 'OXA-48 and VIM-5' were demonstrated in two Klebsiella pneumoniae isolates. The total clustering rate was 20.2%. About 69 Klebsiella pneumoniae yielded 60 profiles and 12 isolates formed five clusters. We have demonstrated the presence of OXA-48 carbapenemases in the majority of isolates in a large collection of carbapenemase-producing isolates from a single hospital. The relatively high rates of NDM-1-producing isolates and colistin resistance is noteworthy.